Human rights in the world of animal laborans - Ribas, Christina Miranda (Argumentos - Revista de Filosofia, 2013)
Starting with the distinction/indistinction among the activities of the vita activa (action, work, labor), whose prevalence may be acknowledged, historically, as the organizer of different anthropological conceptions, we try to ponder on the meaning of human rights in the world of the animal laborans, in an attempt to understand them under the theoretical perspective of Hannah Arendt, guided by the Arendtian conception of understanding as a producer of meaning - rooted in the life process - which allows for the reconciliation with human reasons and passions.